2016
DOI: 10.3168/jds.2015-10441
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of individual cow versus group concentrate allocation strategies on dry matter intake, milk production, tissue changes, and fertility of Holstein-Friesian cows offered a grass silage diet

Abstract: A diverse range of concentrate allocation strategies are adopted on dairy farms. The objectives of this study were to examine the effects on cow performance [dry matter (DM) intake (DMI), milk yield and composition, body tissue changes, and fertility] of adopting 2 contrasting concentrate allocation strategies over the first 140 d of lactation. Seventy-seven Holstein-Friesian dairy cows were allocated to 1 of 2 concentrate allocation strategies at calving, namely group or individual cow. Cows on the group stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 46 publications
10
30
0
1
Order By: Relevance
“…Moreover, only 1% of the cows ate more than 7.5 kg of DM/d in concentrates even though the maximum limit of concentrate allowance was 8.6 kg of DM/d. Total DMI did not differ between the 2 concentrate strategies, supporting previous studies where concentrate allocation was based on the level of individual yield or energy balance (Maltz et al, 2013;Little et al, 2016;Purcell et al, 2016). However, the individual cow concentrate strategy increased the concentrate intake by 1 kg during mid lactation and 0.7 kg during late lactation compared with the control strategy for both breeds.…”
Section: Feed Intakesupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, only 1% of the cows ate more than 7.5 kg of DM/d in concentrates even though the maximum limit of concentrate allowance was 8.6 kg of DM/d. Total DMI did not differ between the 2 concentrate strategies, supporting previous studies where concentrate allocation was based on the level of individual yield or energy balance (Maltz et al, 2013;Little et al, 2016;Purcell et al, 2016). However, the individual cow concentrate strategy increased the concentrate intake by 1 kg during mid lactation and 0.7 kg during late lactation compared with the control strategy for both breeds.…”
Section: Feed Intakesupporting
confidence: 80%
“…However, other studies showed that milk production did not improve for cows fed an individual cow concentrate strategy based on weekly milk yield compared with either a PMR with a fixed amount of concentrate or a group strategy with TMR feeding (Little et al, 2016;Purcell et al, 2016). In contrast, an individual cow concentrate strategy based on the calculated energy balance and applied as a TMR to Holstein cows in early lactation improved milk production compared with a standard TMR (Maltz et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Supporting this response, previous studies reported enhanced milk production as a result of increased energy intake (Erickson et al, 1992;Chouinard et al, 1997;Moallem et al, 2000). However, other studies reported no effect on milk yield when feeding enriched starch-or fat-based diets or combinations (Garnsworthy et al, 2008b;Gilmore et al, 2011;Little et al, 2016). These researchers suggested that the lack of a significant effect on milk production could be attributed to the use of isocaloric diets in the studies.…”
Section: Effect Of Energy Sources On Milk Yield and Milk Compositionmentioning
confidence: 44%
“…However, important enhancements in conception rates were observed when feeding a diet that increased glucose and insulin levels in the early postpartum period and then switching to a diet that reduced insulin levels during the mating period, compared with other treatments (Garnsworthy et al, 2009). Furthermore, pregnancy rates for first and second services were enhanced when grass silage was supplemented with a similar concentrate fed to cows individually, based on the milk yield of the previous week, compared with those on a mixed diet containing grass silage and concentrate in a 50/50 ratio on a DM basis (Little et al, 2016). In contrast, Gilmore et al (2011) found no improvements in pregnancy rates when feeding a glucogenic diet in early lactation to encourage the resumption of oestrus followed by a lipogenic diet to promote embryonic development, compared with other treatments.…”
Section: Effect Of Energy Sources On Reproductive Efficiency Of Dairymentioning
confidence: 76%
See 1 more Smart Citation